Difficulties facing ulis students in approaching terminology in English for economics course = Khó khăn của sinh viên ĐHNN trong việc tiếp cận thuật ngữ của khóa học Tiếng Anh kinh tế - Phạm, Thị Xuân Quỳnh (2021)
Nowadays, with the development of globalization and economic integration, economics and the related issues have become one of the most-mentioned topics worldwide. Therefore, English for Specific Purposes (ESP) has been a promising branch in English Language Teaching. The purpose of ESP course is to supply learners English language used in Economics, which typically presented by terminology. While much effort focus has been put on translation of terminology, difficulties for linguistic students in learning economic terms have not been drawn full proper attention yet. By highlighting the lack of related studies in the ESP setting in Vietnam, this paper is one among the first studies on the linguistic students‟ learning terminology through their difficulties, causes and solutions. Thanks to a flexible combination of quantitative and qualitative methods, valid results can be yielded from the study. Questionnaire was used as a data collection instrument to indentify the most common challenges in three processes of learning term including understanding, remembering, and applying. 30 fourth-year students were chosen as the participants of the study. They were classified into two groups which are double degree program students and mainstream students who major in English Language Teaching. The reasons for their difficulties were categorized into internal causes, and external ones. Solutions suggested by students and teachers were also provided in the thesis.